Introducing Constraint Well-Founded Semantics for Constraint Logic Programming Through Rewriting Transformations - Garreau, Bryan; Lodeiro, Martin Dieguez; Monfroy, Eric; Stephan, Igor (Proceedings - International Conference on Tools with Artificial Intelligence, TAI, 2024)
Constraint Answer Set Programming (CASP) combines Answer Set Programming (ASP) and Constraint Programming (CP) to offer a powerful framework for solving complex problems. While there exists various ways to represent CASP problems, fusing both in a way that benefits both communities remains difficult to this day. To address this, we propose to extend the Well Founded Semantics (WFS) to propositional constraint logic programs. To this end, we present an iterative process involving elementary rewriting transformations to simplify the program iteratively. Our method aims to give a better description of the interactions between ASP and CP inside of a constraint logic program.